The Effect of the Intervention Islamic Resilience Model on Blood Pressure and Spiritual Well-Being of Hypertensive Patients - Sukarmin, Sukarmin; Nurachmah, Elly; Yona, Sri; Gayatri, Dewi; Aryani, Ratna; Awaludin, Sidik (Jurnal Keperawatan Soedirman, 2025)
Hypertension remains a disease that poses a problem in all countries. WHO reports that there are still 1.28 billion hypertensive patients worldwide. The aim of this study was to determine the effect of Islamic emotional resilience on blood pressure and spiritual well-being. This study used the RCT method involving 100 hypertensive patients, consisting of 50 respondents in the intervention group and 50 in the control group. The intervention group received an Islamic resilience model intervention for 3 weeks, while the control group continued taking antihypertensive medication. The study results showed a significant effect of the Islamic emotional resilience model on systolic blood pressure (p = 0.00), diastolic blood pressure (p = 0.00), and spiritual well-being (p = 0.00). In the control group, there was a significant difference in systolic blood pressure before and after (p = 0.00), diastolic blood pressure (p = 0.00), and spiritual well-being (p = 0.129). Islamic emotional resilience serves as an important complementary measure in the management of hypertensive patients